148k views
2 votes
If f(x) = -3 and g(x) = 4x2 + x - 4, find (f+9)(x).

2
A.
X
-1
A. 4x2 + 2x-1
B. 4x2 +
-7
C. 4x2 +2x-1
7
X-1
D. 6x2 - 7

If f(x) = -3 and g(x) = 4x2 + x - 4, find (f+9)(x). 2 A. X -1 A. 4x2 + 2x-1 B. 4x-example-1
User Larsrh
by
5.1k points

1 Answer

2 votes

Explanation:

(f+g)(x) = f(x) + g(x) =

x/2 - 3 + 4x² + x - 4 = 4x² +3x/2 - 7

so, yes, B is the right answer.

User Noam M
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.